Impact of HLA matching and HLA antibodies in organ transplantation: a collaborative transplant study view - Süsal, Caner; Opelz, Gerhard (Immunogenetics, 2012)
The Collaborative Transplant Study (CTS) was initiated in 1982 in Heidelberg, Germany, and originated from the need to gain further insight into the complex problems and risks involved in human organ transplantation. Currently, more than 400 transplant centers in 45 countries are contributing to this voluntary international effort, and from the beginning of the study, the impact on graft outcome of immunological factors, such as matching for HLA antigens and allosensitization to HLA and non-HLA antigens, have been areas of interest. Herein, we summarize the recent findings from the CTS on these two topics.
Gesehen am 21.07.2020